The impact of marketing orientation on improving the quality of service applied research in some Iraqi mobile phone companies - جثير سعدون حمود; فيصل شروق جاسم (Journal of Economics and Administrative Sciences, 2017)
The research discusses two variables are important, orientation marketing and quality of service, and that the purpose of the research is to see whether the telecom companies applied orientation marketing or not and to what extent is keen to apply it to suit the Iraqi environment as it has been applied research in kork Telecom company and Asia Cell Telecom are sectors service job in the business sector in Iraq, The information was obtained through the design of the questionnaire compatible runway Likert, and distribution (92) questionnaire, which (50) for the company Korek Telecom and (42) of the Asia-Cell, research population sample included a number of staff in the departments and units in the two companies, it has been supporting the the questionnaire with the help of interviews and observation were formulating a hypothesis president of research , The researcher used a number of statistical methods and descriptive is) the arithmetic mean, standard deviation, variance, coefficient of variation, simple regression equation based on statistical Spss program, The researcher reached to the group’s conclusions most notably the the presence of the effect of marketing trend in the quality of service, Notable among recommendations researcher concluded by that the search was for the surveyed companies need to focus their efforts in the development-oriented marketing through to pay attention and focus on providing quality service and taking into consideration the activities related to the service.